1996
DOI: 10.1074/jbc.271.37.22499
|View full text |Cite
|
Sign up to set email alerts
|

Role of Proximal Promoter Elements in Regulation of Renin Gene Transcription

Abstract: Mouse As4.1 cells, obtained after transgene-targeted oncogenesis to induce neoplasia in renal renin-expressing cells, express high levels of renin mRNA from the endogenous Ren-1(c) gene. We have used these cells to characterize the role of the Ren-1(c) proximal promoter (+6 to -117) in the regulation of renin gene transcription. It was found that 4.1 kilobases (kb) of Ren-1(c) 5'-flanking sequence, in combination with the proximal promoter, are required for strong activation (approximately 2 orders of magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
114
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 52 publications
7
114
0
Order By: Relevance
“…Through deletion analysis of the 5Ј-flanking sequence of the Ren-1c gene, we identified two short DNA fragments in the gene promoter that are sufficient to mediate the transcriptional repression. The proximal fragment is the minimal Ren-1c gene promoter, and the distal fragment is within a 242-bp enhancer previously identified to be important for basal renin expression (8). Most recently, this enhancer was shown to be critical for the control of renin expression in vivo, and mice lacking this enhancer have renin depletion in JG cells and develop low blood pressure (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through deletion analysis of the 5Ј-flanking sequence of the Ren-1c gene, we identified two short DNA fragments in the gene promoter that are sufficient to mediate the transcriptional repression. The proximal fragment is the minimal Ren-1c gene promoter, and the distal fragment is within a 242-bp enhancer previously identified to be important for basal renin expression (8). Most recently, this enhancer was shown to be critical for the control of renin expression in vivo, and mice lacking this enhancer have renin depletion in JG cells and develop low blood pressure (39).…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic studies have demonstrated that the cis-DNA elements required for the tissue-specific and developmental stage-specific expression as well as for response to a variety of physiological stimuli are located within 5 kb of the 5Ј-flanking region of the murine renin gene (5)(6)(7). In the 4.1 kb 5Ј-flanking region of the Ren-1c gene, a proximal minimal promoter (Ϫ117 to ϩ6) and a potent 242-bp enhancer (Ϫ2866 to Ϫ2625) upstream of the transcriptional start site have been shown to be necessary for a high level expression of the renin gene in As4.1 cells (8). Recent studies have revealed the involvement of multiple regulatory proteins in the regulation of renin expression, which include nuclear receptors LXR ␣ and ␤ (9, 10), Ear2 (11), and RAR/RXR complex (12), and transcription factors CREB/CREM and USF1/USF2 (13,14), HOXD10-PBX1b complex and Est-1 (14,15), Sp1/Sp3 (16), and NF-Y (17).…”
mentioning
confidence: 99%
“…Our results show that the KE is dispensable for these functions, but is required for the maintenance of base-line levels of hREN mRNA. The KE was originally identified as a sequence that strongly stimulated activity of the renin promoter in As4.1 cells, a renin expressing cell line derived from the kidney with many properties of JG cells (9). Mutational and biochemical analysis revealed the enhancer to contain the binding sites for CREB, CREM, RAR␣/RXR, USF1/2, NFI, and SP1/3, all of which are required to maximally stimulate transcriptional activity of the renin promoter (12,14,16).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by us and others have identified a potent transcriptional enhancer 2.6 kb upstream of the mouse Renin (mRen) gene (9). A sequence with 75-85% homology was also identified ϳ6 kb upstream of the rat and 11-kb upstream of the human RENIN (hREN) gene (10,11).…”
mentioning
confidence: 91%
“…Two alleles from each of the 2 murine renin loci were compared throughout the sequenced region of the Ren-2 h allele ( Figure 2). Sequences for Ren-1 c (L78789) and Ren-1 d (M32352) were retrieved from GenBank, 14,15 whereas the sequence for Ren-2 h was derived from pGEMR2H-5, and the sequence for Ren-2 d was derived from pCATNOT R2-4.6. As noted above, the M3 element is present in both Ren-1 and Ren-2 loci, whereas the B2 element is found in the alleles of Ren-2 and not in the alleles of Ren-1.…”
Section: Abonia Et Al Nre Mediated Expression Of Murine Renin Genes 107mentioning
confidence: 99%